PENGEMBANGAN MEDIA PERMAINAN MONOPOLI BERBASIS NILAI AGAMA DAN MORAL ANAK USIA 5-6 TAHUN DI PAUD SALSABILA T.A 2022/2023 - Milwana Harahap; Dewi Fitria (ALFIHRIS : Jurnal Inspirasi Pendidikan, 2023)
The problem found in this study is the lack of variety of media that supports children's learning processes according to the characteristics of children in the development of religious and moral values related to the ability to learn religious and moral values in children aged 5-6 years. This study aims to produce monopoly game media based on religious and moral values that are in accordance with the characteristics of group B children in PAUD Salsabila. The type of research used is research and development (R&D) using seven development steps, namely problem identification, information gathering, product design, product revision, small-scale product testing, and second product revision. The research design used was a pre-test and post-test design with the same group to find out how to improve children's ability to memorize readings and prayer movements in children aged 5-6 years at PAUD Salsabila